Three-stage anaerobic co-digestion of food waste and horse manure - Jingxin Zhang (Scientific Reports, 2017)
Abstract A novel compact three-stage anaerobic digester (HM3) was developed to combine the advantages of high solids anaerobic digestion (AD) and wet AD for co-digestion of food waste and horse manure. By having three separate chambers in the three-stage anaerobic digester, three different functional zones were created for high-solids hydrolysis, acidogenesis and wet methanogenesis. The results showed that the functionalized partitioning in HM3 significantly accelerated the solubilization of solid organic matters and the formation of volatile fatty acids, resulting in an increase of 11~23% in methane yield. VS reduction in the HM3 presents the highest rate of 71% compared to the controls. Pyrosequencing analysis indicated that different microbial communities in terms of hydrolyzing bacteria, acidogenic bacteria and methanogenic archaea were selectively enriched in the three separate chambers of the HM3. Moreover, the abundance of the methanogenic archaea was increased by 0.8~1.28 times compared to controls.